1154. Comparison of Five Testing Modalities for the Assessment of Patient Environment Cleanliness. (26th November 2018) - Salsgiver, Elizabeth; Martin, Elena; Callan, Katrina; O'Hara, Niamh B; Ounit, Rachid; Westblade, Lars F; Mason, Christopher E; Simon, Matthew S; Saiman, Lisa; Furuya, E Yoko; Calfee, David P
Abstract: Background: Microbial contamination of the patient environment has been associated with healthcare-associated infections. Objective assessment of environmental cleanliness is recommended by the CDC to identify improvement opportunities. Methods currently used to assess cleanliness and microbial dynamics differ in their sensitivity, specificity, cost, ease of use, and turnaround time. We compared five assessment methods to examine these characteristics. Methods: The bedrail, overbed table, remote control, and toilet seat in occupied patient rooms were sampled and assessed with: adenosine triphosphate (ATP) luminescence technology (LT), Replicate Organism Detection And Counting (RODAC) plates, C diff Banana Broth™ (CDBB), conventional aerobic culture (CC) and antimicrobial susceptibility testing, and shotgun next-generation sequencing (NGS) and analysis using metagenomic software. Results: One hundred forty surfaces from 35 rooms were sampled. Of 70 surfaces sampled by both ATP LT and RODAC, 42 (60%) had concordant "pass" or "fail" results. Of 28 discordant samples, 26 (93%) passed by RODAC but failed by ATP LT. CDBB testing identified Clostridioides difficile on two surfaces in one room; C. difficile was also identified by NGS in this room. NGS had 100% concordance with organisms identified by CC, and identified approximately 20 additional organisms not identified by CC per surface. 38% of organisms identified by NGS were potential pathogens, compared with 13% through CC. No correlations were found between the primary quantitative assessments (RODAC bacterial concentrations and ATP LT ATP concentrations) and quantitative components of CC (presence/absence of organisms) and NGS (read numbers). Conclusion: ATP LT and RODAC plates both provide useful quantitative cleanliness data, although high ATP values did not always indicate the The presence of viable aerobic bacteria. CDBB may be a useful method for identifying C. difficile in the environment, but larger studies of the performance characteristics of CDBB are needed. CC and NGS provided useful organism identification information, but NGS had higher sensitivity for detecting potentially pathogenic organisms. The clinical implications of NGS results must be further studied and cost and technical expertise are important considerations. Disclosures: N. B. O'Hara, Biotia: Board Member, Employee and Shareholder, Salary. L. F. Westblade, Accelerate Diagnostics: Grant Investigator, Grant recipient. Biomerieux: Grant Investigator, Grant recipient. Allergan: Grant Investigator, Grant recipient. Merck: Grant Investigator, Grant recipient.